Impacts of Impaired Vision and Eye Diseases on Vision-Related Quality of Life in Indonesia - Asroruddin, Muhammad; Artini, Widya; Gondhowiarjo, Tjahjono D; Rahayu, Tri; Lestari, Yeni D (UI Scholars Hub, 2017)
Background: To determine the impacts of visual impairment and eye diseases on vision-related quality of life (QoL) in populations with severe visual impairment (SVI) and blindness in Indonesia. Methods: A cross-sectional study was conducted on 134 respondents from, 5 different provinces, simultaneously with a validation study using data from the 2013 National Basic Health Survey. Participants aged ≥ 18 years with visual acuity of < 6/60 underwent an ocular examination and guided interview. The impact of vision impairment related to their QoL was assessed using the NEI-VFQ 25 questionnaire. The scores were then compared between participants with blindness (< 3/60) and participants with SVI (> 3/60 to < 5/60), and the causes of visual impairment. Results: Severe visual impairment and blindness were mostly found in productive aged females with lower education and income levels, and cataracts were the leading cause. Vision-related quality of life was lower in the blind group compared to the SVI group (p = 0.001). The impacts of visual impairment related mostly to distance activities (p = 0.007), social functions, and near activities (p = 0.002). NEI-VFQ 25 scores were lower in glaucoma respondents than cataract respondents. Conclusions: Results suggest that subjects with blindness had a lower total QoL score than those with SVI, in addition to the subscale scores. Furthermore, glaucoma disease had the lowest QoL score.